Age hardening and precipitation behavior of an experimental cast Al-Mg-Si alloy treated by T6 and T6i6 heat treatments - Imurai S. (2014)
An experimental Al-7.32wt%Si-0.3wt%Mg alloy equivalent to cast A356 Al-Mg-Si alloy was studied. Age hardening was performed by two artificial ageing heat treatments, T6 and T6I6. Vickers microhardness was measured within the dendritic regions. It was found that peak ageing was reached after about 24 hours. T6 and T6I6 increased the hardness from the as-cast value by 52% and 60%, respectively. The peak hardness achieved via T6I6 is approximately 8% higher than that obtained by T6. Overall microstructure was studied by scanning electron microscopy and energy dispersive x-ray spectrometry. Eutectic constituents were revealed as Si flakes and Fe-bearing intermetallic compounds including n-Chinese script phase (Al8Mg3FeSi6) and P(Al5FeSi). Precipitation behavior was investigated by transmission electron microscopy and the precipitation sequence found was somewhat in agreement with those reported previously for wrought and cast Al-Mg-Si alloys. However, the peak hardness ageing period coincided with the presence of Β″ phase or its precursors, not Β′ phase.